Environmentally friendly processes for the production of silver nanoparticles - Jain, Nidhi; Dani, Kartik; Chaskar, Sahil; Noor, I. M.; Yahya, M. Z.A.; Koul, Aditya; Khatkepatil, Revannath (John Wiley and Sons, 2025)
The development of sustainable and robust methods for producing nanoparticles is a major turning point in the field of nanotechnology. Silver nanoparticles are important because of their features, which include improving the physical, chemical, and structural qualities vis-a-vis their bulk equivalent and the ensuing applications. The various applications of silver nanoparticles (Ag NPs) and their green manufacturing methods are covered in this review, bearing in mind the aforementioned points. This study also emphasized that how important it is to optimize synthesis factors like temperature, pH, and concentration in order to obtain the appropriate attributes for nanoparticles. Then, the possible uses of silver nanoparticles produced through green synthesis are explored. These uses included antimicrobial coatings, medication delivery systems, and environmental cleanup. It establishes the foundation for upcoming studies and advancements in the area of green nanotechnology, fostering a more sustainable future.